Effect of Irrigation Frequency and Depth on Yield and Water Productivity of Field Pea at Koga and Rib Irrigation Scheme, Ethiopia - Tewabe, Dires (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Efficient irrigation scheduling is crucial for optimizing crop yield and water productivity, particularly in water-scarce regions. This study evaluated the effects of different irrigation frequencies and depths on the yield and water productivity of field pea (Pisum sativum L.) at the Koga and Rib irrigation schemes in Ethiopia over two growing seasons. A factorial experiment with two irrigation intervals (10 and 14 days) and five irrigation depths (50%, 75%, 100%, 125%, and 150% of crop water requirement) was conducted using a split-plot design with three replications. The results revealed that irrigation scheduling significantly influenced both grain yield and water productivity at both sites. At Koga, the highest grain yield (2.12 t ha⁻¹) and optimal water productivity (0.55 kg m⁻³) were achieved by irrigating at 100% crop water requirement (CWR) every 10 days. Conversely, at Rib, the highest yield (3.21 t ha⁻¹) and water productivity (1.05 kg m-3) were obtained with 75% CWR applied every 10 days. Increasing irrigation depth beyond these optimal levels did not further enhance yield and led to a decline in water productivity. These findings suggest that site-specific irrigation scheduling is essential for maximizing field pea production while improving water use efficiency. The study recommends irrigating field pea at 100% CWR every 10 days in Koga and 75% CWR every 10 days in Rib to achieve the best balance between yield and water conservation.Keywords: Irrigation Scheduling, Water Productivity, Field pea, Crop Water Requirement